“We care about feminist notions of genuine security” A Conversation with Margo Okazawa-Rey - Meyer, Katrin (My University, 2020)
Margo Okazawa-Rey is Professor Emerita at San Francisco State University. Her research develops an understanding of security from an intersectional, transnational, and activist perspective. She examines the connections between militarism, economic globalization and the impacts on local and migrant women in East Asia, as well as the role of feminist research in activism, women’s empowerment and policy change. She was a founding member of the Combahee River Collective, which articulated a theory of intersectionality in the 1970s. The following interview with Margo Okazawa-Rey took place on September 24, 2019 by video call.
Keywords: Feminismus; Sicherheit; ddc:320